CEMARAN KAPANG PADA PAKAN DAN PENGENDALIANNYA - Riza Zainuddin Ahmad (Jurnal Penelitian dan Pengembangan Pertanian, 2009)
The contamination of mold in feed and its controlThe contamination of some kinds of mold as Aspergillus spp., Fusarium spp., Penicillium spp., and Mucor spp. can be found in feed and feedstuff especially corn. The contamination causes health disturbance of animals. The disease is not only caused by the mold, but also by toxin produced. Health loss in term of economy due to the mold contamination is quite significant. Some factors can support the appearance of mold and toxic contamination in feed, especially humidity and temperature. In Indonesia, Aspergillus sp. especially A. flavus is the dominant mold contaminant in feed. Controlling as prevention by early detection or visual inspection and good management is a better choice compared to cure.